GROWTH PERFORMANCE AND MINERAL STATUS ON GOATS (Capra hircus Linn.) SUPPLEMENTED WITH ZINC PROTEINATE AND SELENIUM YEAST - Maharani Aditia; Sunarso Sunarso; C.C. Sevilla; A.A. Angeles (Chemical Engineering Diponegoro University, 2014)
Twenty two (22) doelings weighing 7.86 ± 2.12 kg were grouped into 6 weight classes in a feeding trial to determine the effects of dietary zinc proteinate and selenium yeast on mineral status and growth performance. The Zn-supplemented groups received 200 mg additional Zn daily from chelated Zn proteinate, an insoluble powder containing 15% elemental Zn. Se-supplemented groups received 3 mg Se from Se yeast consisting mainly of selenomethionine (63%). The four (4) dietary treatments were as follows: T1 : 0 mg Zn + 0 mg Se; T2: 0 mg Zn + 3 mg Se; T3 : 200 mg Zn + 0 mg Se. T4: 200 mg Zn/head + 3 mg Se/head. The experiment was conducted in a 2 x 2 factorial design in RCBD. Napier grass used in the trial contained 89.03 ppm Zn, while the mixture of corn-soybean oil meal had Zn content 49.73 ppm. Supplementation of Zn and Se in the diets composed of 60% Napier and 40% soya-corn mix had no effect on dry matter intake, body weight gain, and feed efficiency. Giving 200 mg Zn/head tends to increase (P<0.05) the Zn concentration in the blood of doelings among the levels of Se. Percent digestibility of Zn decreased with Zn supplementation at 200 mg. Percent apparent digestibility of Zn tends to be higher in animals without mineral supplementation. Results indicate that Zn and Se supplementation did not affect growth performance. Zn supplementation increased blood Zn concentration, but did not affect digestibility of Zn.